Molecular aspects of papillary thyroid carcinoma (Research, Society and Development, 2023)
Introduction: Thyroid cancer is the most common endocrine neoplasm. The pathogenesis of thyroid cancer considers mutations leading to progression through a process of dedifferentiation generating well-differentiated carcinomas, such as papillary and follicular, and progressing to poorly differentiated, undifferentiated or anaplastic thyroid carcinomas. Objective: To describe the main molecular alterations for the development of PTC. Methodology: This is a narrative review. The databases PUBMED, SCIELO, Science Direct, Google Scholar and the National Cancer Institute were used. As inclusion/exclusion criteria, articles comprised between 2004 and 2022, in Portuguese and English. Results and discussion: PTC molecular alterations arise from the initial mutation in some gene involved in the regulation of proliferation and/or cell differentiation, leading to clonal expansion of the genetically modified cell due to its ability to proliferate and escape cell cycle control through changes in genes such as BRAF, KRAS, NTRK1 and RET. Conclusion: The onset and progression of thyroid cancer comprises multiple genetic changes, including mutations that lead to activation of MAPK and PI3K-AKT signaling pathways. Altered genes that affect this pathway include mutations in genes encoding RAS and BRAF intracellular signal transducers and rearrangements in RET/PTC receptor tyrosine kinase. These data are extremely important for understanding the pathophysiological mechanism of this condition, as well as providing the basis for a more assertive diagnosis and more specific treatment, providing a more favorable prognosis with fewer side effects.